Madrasah Movement with Character: Optimizing the Implementation of P5RA Values through MI Teacher Mentoring - Nur Hakim; Muhammad Nizam Zakhman Al Farabi (GUYUB: Journal of Community Engagement, 2025)
The success of madrasahs can be measured through positive changes in student learning patterns that are enjoyable and aimed at producing intellectually, spiritually, and morally competent generations based on the values of Pancasila and Islam rahmatan lil ‘alamin. The implementation of the Pancasila Student Profile Strengthening Project Rahmatan Lil Alamin (P5RA) in madrasahs under KKMI Paciran, Lamongan, was carried out through optimizing teacher mentoring programs. This mentoring aims to strengthen teachers’ abilities in understanding, planning, and integrating P5RA values into the learning process. The Asset-Based Community Development (ABCD) approach was used to explore the human resources potential of each madrasah. Data collection techniques included observation, interviews, and documentation, with teachers as the primary data sources, and madrasah principals and the Head of KKMI as secondary sources. The results showed a significant increase in P5RA implementation, rising by 26%, from 68% to 94% of madrasahs. The success indicators include teachers’ improved ability to integrate the values of religious moderation, tolerance, and social care into both classroom learning and school culture. Supporting factors include the commitment of school leadership, collaboration among teachers, and active community participation. However, challenges remain, particularly the limited human resources, requiring ongoing assistance and capacity building